CONSTRUCTION PROJECT MANAGEMENT FOR BEGINNERS - Shamsulakmar Abdul Munir,; Noor Khazanah A Rahman, (2026)
This book is written to address these challenges by providing practical and actionable steps for both aspiring and practicing construction managers. Readers will also find valuable insights on coordinating with all stakeholders-clients, contractors, consultants, suppliers and regulators- to ensure smooth project execution. By summarizing the fundamental knowledge required in project supervision, this book aims to equip readers with the tools and confidence to manage projects effectively. Whether you are a student preparing for a career in construction, a beginner taking your first steps as a project manager, or a professional seeking to strengthen your skills, the content here is designed to support your growth. Ultimately, the success or failure of a construction projects rests heavily on the project manager’s competence and leadership. We hope this book will serve as a reliable guide for those committed to delivering projects that meet quality, cost and schedule expectations-while upholding integrity, safety and professionalism in every step of the journey.